2013
DOI: 10.1038/npp.2013.154
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Amyloid-β Immunotherapy Trials in Alzheimer’s Disease

Abstract: Drug candidates directed against amyloid-β (Aβ) are mainstream in Alzheimer's disease (AD) drug development. Active and passive Aβ immunotherapy is the principle that has come furthest, both in number and in stage of clinical trials. However, an increasing number of reports on major difficulties in identifying any clinical benefit in phase II-III clinical trials on this type of anti-Aβ drug candidates have caused concern among researchers, pharmaceutical companies, and other stakeholders. This has provided cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 108 publications
0
47
0
Order By: Relevance
“…CSF biomarkers are increasingly important in AD diagnosis [3] and clinical trials [1, 34]. However, their use is currently limited by methodological variability and subsequent inconsistency in the cut-off values used to interpret results [35].…”
Section: Discussionmentioning
confidence: 99%
“…CSF biomarkers are increasingly important in AD diagnosis [3] and clinical trials [1, 34]. However, their use is currently limited by methodological variability and subsequent inconsistency in the cut-off values used to interpret results [35].…”
Section: Discussionmentioning
confidence: 99%
“…Many disease-modifying therapeutic agents being developed target amyloid generation, deposition, or clearance [17]. Recent phase III trials targeting amyloid have reported that approximately 20% of trial participants actually had little or no Aβ when studied later using such PET imaging (suspected nonamyloid pathologic findings) [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is quite possible that some of the reasons for the apparent disconnect between preclinical and clinical results may be the testing of the drug candidate in patients in which more extensive neurological insults are apparent. Changes in clinical trials of potential Alzheimer's Disease drugs have prompted the inclusion of subjects with early signs of the disease identified by biological markers and subject registries (Blennow et al, 2014;Cummings et al, 2016).…”
Section: Geneticsmentioning
confidence: 99%